Postmortem Studies of Fetal Grafts in Parkinson’s Disease: What Lessons Have We Learned? - Jia-Yi Li; Jia-Yi Li; Wen Li; Wen Li (Frontiers in Cell and Developmental Biology, 2021)
Neural transplantation is a potential therapeutic method for Parkinson’s disease (PD). Fetal dopaminergic (DA) neurons have been important transplantation cell sources in the history of replacement therapy for PD. Several decades of preclinical animal experiments and clinical trials using fetal DA neuron transplantation in PD therapy have shown not only promising results but also problems. In order to reveal possible factors influencing the clinical outcomes, we reviewed fetal DA neuron transplantation therapies from 1970s to present, with a special focus on postmortem studies. Firstly, we gave a general description of the clinical outcomes and neuroanatomy of grafted cases; secondly, we summarized the main available postmortem studies, including the cell survival, reinnervation, and pathology development. In the end, we further discussed the link between function and structure of the grafts, seeking for the possible factors contributing to a functional graft. With our review, we hope to provide references for future transplantation trials from a histological point of view.